Qfwfq between Alcina's island and Atlante's palace:: An Intertextual Analysis of Italo Calvino's The Origin of Birds (ENTHYMEMA, 2025)
The first edition of Calvino's L’origine degli uccelli was published in "Linus" in July 1967. It was illustrated by Emilio Tadini, whose works suggest a relationship between the tale and L’Orlando furioso. In fact, on the one hand, Calvino takes themes, images, even specific words from Ariosto, and he reuses them both in L’origine degli uccelli as in other writings, starting with his work on the Furioso for Italian radio also in 1967. On the other hand, this process reveals a deep reflection on the literary relationship between fiction and reality.Keywords – Italo Calvino; Contemporary Italian Literature; Ludovico Ariosto; Intertextuality; Emilio Tadini.
Keywords: Italo Calvino; Contemporary Italian Literature; Ludovico Ariosto; Intertextuality; Emilio Tadini